2007
DOI: 10.1124/mol.107.039321
|View full text |Cite
|
Sign up to set email alerts
|

An Intracellular Allosteric Site for a Specific Class of Antagonists of the CC Chemokine G Protein-Coupled Receptors CCR4 and CCR5

Abstract: A novel mechanism for antagonism of the human chemokine receptors CCR4 and CCR5 has been discovered with a series of small-molecule compounds that seems to interact with an allosteric, intracellular site on the receptor. The existence of this site is supported by a series of observations: 1) intracellular access of these antagonists is required for their activity; 2) specific, saturable binding of a radiolabeled antagonist requires the presence of CCR4; and 3) through engineering receptor chimeras by reciproca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
97
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(104 citation statements)
references
References 35 publications
6
97
0
Order By: Relevance
“…Although it may seem counterintuitive that a ligand fits partially in the entrance channel of the TM domain, recent advances in CXCR2-ligand binding pocket elucidations have shown that an intracellular binding site for CXCR2 antagonists exists as well (Nicholls et al, 2008;Salchow et al, 2010), a result seen only for two other GPCRs, the chemokine receptors CCR4 and CCR5 (Andrews et al, 2008). As such, this does not only imply that CXCR2 behaves differently from other GPCRs, but it could also mean that we should be thinking outside of the metaphoric box that is the TM domain.…”
Section: Discussionmentioning
confidence: 99%
“…Although it may seem counterintuitive that a ligand fits partially in the entrance channel of the TM domain, recent advances in CXCR2-ligand binding pocket elucidations have shown that an intracellular binding site for CXCR2 antagonists exists as well (Nicholls et al, 2008;Salchow et al, 2010), a result seen only for two other GPCRs, the chemokine receptors CCR4 and CCR5 (Andrews et al, 2008). As such, this does not only imply that CXCR2 behaves differently from other GPCRs, but it could also mean that we should be thinking outside of the metaphoric box that is the TM domain.…”
Section: Discussionmentioning
confidence: 99%
“…Given the large size of this binding pocket, the two different binding sites that we have identified for CCR2 could both be located in this transmembrane region. In addition, an allosteric binding site on the intracellular side of the receptor in the C-terminal domain has been identified for the chemokine receptors CXCR2, CCR4, and CCR5 (Andrews et al, 2008;Nicholls et al, 2008;Salchow et al, 2010). This binding site resides close to the site of G protein-coupling to the receptor, and therefore it is assumed that activation of the G protein is prevented in the presence of an antagonist at this site.…”
Section: Discussionmentioning
confidence: 99%
“…These chemokine inhibitors are thought to act at a binding site within or adjacent to the G-protein-binding pocket. [42][43][44] Mutational studies suggest that different classes of G-proteins associate with different regions on the cytoplasmic face of PAR1. 45 Parmodulins could bind at or near the G-protein-binding pocket and selectively compete with Ga q , but not Ga 12/13 .…”
Section: Discussionmentioning
confidence: 99%